"How much is that player in the window? The one with the early birthday?" Relative age influences the value of the best soccer players, but not the best businesspeople - Furley, P.; Memmert, D.; Weigelt, M. (Frontiers in Psychology, 2016)
Although people in general tend to attribute success to individual merit (see e.g., Gilbert and Malone, 1995) research has shown that something as trivial as the date of a person's birth can have—under certain circumstances—a major impact on an individual's achievement. The Canadian psychologist Roger Barnsley (Barnsley et al., 1985) made the extraordinary discovery that the great majority of top-level athletes were born within the first months of the year, whereas a lot less players playing at the highest level were born later in the year (Dudink, 1994; Edwards, 1994; Cobley et al., 2009). This skewed birthdate distribution was termed Relative Age Effect. The assumed explanation for this effect was simple and had nothing to do with Astrology, but instead was attributed to the fact that children and youth athletes are divided into age-groups according to their birth date (usually with the cutoff date being the first of January). This early selection cutoff date can lead to a maturation head start of almost a year within an age group. It is further assumed that this maturation head start will result in a Matthew effect ("the rich get richer; the poor get poorer," see e.g., Merton, 1957) due to better developmental circumstances, such as better coaching, more playing and practice time. Indeed, research suggests that coaches have more favorable attitudes toward more matured players (Furley and Memmert, 2015) and that maturation advantages have the potential to translate to performance advantages (Buchheit and Mendez-Villanueva, 2014; Gastin and Bennett, 2014). As a consequence, the most successful athletes are likely to show a skewed birthdate distribution (see e.g., Helsen et al., 2012 for a recent demonstration), whereas success in other domains without early selection processes involving cutoff dates should not show a skewed birthdate distribution as individuals have equal opportunities to develop (Barnsley et al., 1985).